قید و سزا کا نظام: رواج نامۂ سوات میں موجود والئی سوات کے فرامین کا شرعی و تحقیقی جائزہ: Justice Behind Bars: An Analytical Review of the Walī of Swat’s Decrees on Prisoners’ Rights with a Comparative Study of Islamic Law and Local Legal Frameworks (Al-Qamar, 2025)
This research critically examines the decrees and administrative orders issued by the Wali of Swat regarding prisoners, in the context of Islamic jurisprudence (Fiqh al-‘Uqūbāt). The study aims to explore whether these rulings were consistent with the principles of Shari‘ah as derived from the Qur’an, Sunnah, and the classical juristic traditions of the four Sunni schools of law. By employing a descriptive and analytical methodology, the paper investigates primary historical sources, official proclamations, and contemporary accounts from the Swat State era. It highlights how the Wali’s penal system combined elements of traditional Islamic legal thought with local Pashtun customs (ʿUrf). The findings reveal that while many of the Wali’s measures reflected an intention to uphold justice and public order in accordance with Shari‘ah, certain practices—particularly those related to imprisonment conditions and punitive procedures—require critical reassessment in light of Islamic legal ethics and human dignity. The study concludes with recommendations for future Islamic legal frameworks on correctional justice, emphasizing the balance between deterrence, reform, and compassion.
Keywords: Wali of Swat; Prisoners; Islamic Jurisprudence; Penal Law; Shari‘ah Evaluation; Pashtun Customs; Criminal Justice in Islam; Swat State History